PENGARUH METODE ROLE PLAYING TERHADAP HASIL BELAJAR IPS PESERT DIDIK KELAS III SEKOLAH DASAR - Pamuji, Wiwidyo; Sugiyono, Sugiyono; Kresnadi, Heri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis researchaim to determine the effect of the role playing method on the social science learning outcomes of social science students in class III of the East Pontianak 04 State Elementary School.The method used wasan experimental design and nonequevalent control group design research design. The population was all students from two classes totaling 54 people, the sample of this study was the III A class students, amounting to 26 people as the experimental class and the class III B students as the contro class, amounting to 28 people. The data collection technique used was a measurement technique and a data collection tool was a multiple choice written test. Based on data analysis, the results of the experimental class post-test 80,04 avarage and the post-test control average of 74,07. Hypothesis test results using t-test (Polled Variance) obtained t count = 2,993 while for dk (28+26-2 = 52) with a significant level ? = 5% obtained ttable = 1,676, which means tcount> t table, then Ha was accepted, this prove that there was the influence of the application of the role playing method in learning Social Sciences. Based on the results of the calculation of the effect size (ES) obtained ES = 0,57 which is included in the criteria of being, namely 0,57 <0,8. Thus there was the influence of the role playing method on the results of learning social science students in class III of the East Pontianak 04 State Elementary School. Keywords: Influence, Learning,  Learning Outcomes,  Role Playing Method, , Social Sciences.